Utilização do método QFD como indutor de diretrizes para a melhoria da qualidade: um estudo de caso - Wagner, Adriano (2004)
The quality has not been a product differential anymore. It became a primordial element to the maintaining of organizations in the turbulent competitive market, determined by ongoing transformations. This work presents the use of QFD (Quality Function Deployment) as an inductor method of aims for the quality improvement in the activities of production. The study had as aim to use the proposed method in differentiated conditions of its original conception of products development. Or, it was tried to plan the quality from the identification of requirements demanded by collaborators (indoors clients), from INPLASUL – Indústria de Plásticos Sudoeste Ltda to the quality in the productive process of the company. This proposal evidences the importance of the indoor client to the quality of the offered clients to the consumer market, so, from the compilation, analysis and interpretation given by them, it were defined aims to the improvement of quality in the vulnerable points of production system.. The methodology of the work emphasizes four main points: formal group arrangement, the use of the brainstorming technique, research-action strategy, and a realization of case study. The results obtained demonstrate the efficacy of the method’s use to the ongoing improvement of the quality in the productive processes. It also focus the importance of the quality management in a planned and systemic way, in which the commitment from all the collaborators independent of the hierarchical position consists in the elementary factor the quality guarantee and to the maintenance of the company in the disputed national and international socio-economical scenery.